Total reward offerings that attract : an investigation conducted in SMEs - Black, Richard Petrus (Organisational Psychology, 2015)
Orientation : The current global scarcity of highly skilled employees has forced employers to better understand what attracts these kinds of employees, as they are vital to ensure organisational competitiveness and for the continued success of organisations. In the so- called war for talent, small companies believe they are at a disadvantage compared to large corporates in the battle to attract talented employees given limiting or constraining factors associated with being a smaller sized organisation. Research purpose : The purpose of this study was to investigate the relative importance of various reward elements or reward factors that Small or Medium Enterprises (SMEs) can manipulate in order to compile compelling job offers that are attractive to top talent. An ideal total rewards offering for the attraction of skilled employees that capitalises on the strengths that smaller companies possess, will be proposed. Motivation for the study : Retaining highly performing employees is one of the most important factors that contribute to organisational competitiveness. Companies need to understand how they can attract scarce human resources and specifically in the South African context, understand how to attract even scarcer employees from designated demographic groups in order to meet employment equity targets. Small companies find it difficult to compete with large corporations, for example when it comes to employer branding and so feel at a disadvantage when attempting to attract from the same group of employees that corporates also endeavour to attract. Research design : A quantitative research approach was adopted. Convenience and snowball sampling approaches were employed to gather data by means of three different questionnaires. Firstly, employees that recently moved from large corporate positions to positions within SMEs were asked what was offered to them in order for them to accept the job offer at a small company (n=11). These results were used to develop the second questionnaire (i.e. to develop the attributes and levels used in the conjoint tasks). The second and third questionnaires (the conjoint task and total reward questionnaires, respectively) were distributed to working adults in South Africa (n=105). Conjoint analysis was used to identify an ideal talent attraction mix and to assess how employer branding compares to traditional reward elements in talent attraction. Data from the third questionnaire was analysed using descriptive statistics and t-tests. Main findings : The results of the conjoint analysis revealed that respondents valued the possibility of career advancement most, specifically referring to promotion opportunities or overseas assignments. Significant differences in preference between demographic groups were found when considering performance and recognition, remuneration and benefits, and work culture. Work-life balance were ranked second last by all respondents, while employer brand was consistently viewed as the least attractive factor in talent attraction. Practical and/or managerial implications : Conjoint analysis enables the unique identification of both the combination and quantum of elements that make a job attractive for various demographic groups. Companies can utilise these findings when crafting job offers in order to attract different cohorts of candidates. Contribution and/ or value-add : Limited research exists in South Africa that can assist small companies in attracting top talent. The current study succeeded in identifying that small companies can attract top talent by capitalising on strengths they possess and furthermore assist SMEs to craft compelling job offers for different cohorts of candidates.